The Success of A National Leader - Radovanović, Tihomir (Napredak, 2022)
National leadership as a segment of general leadership belongs to the social science of management that deals with the law of political guidance of given countries, particularly including the revealed causality of the result analogy in the country’s development and the ruling competencies of its leader. That is why, according to general implications, such causality is very important both to the given country and to the overall present and future world. That segment of science has not been thoroughly researched to date because it seems to be clear and therefore should not be studied in further detail. However, in today’s turbulent world, full of huge existential problems (war, terrorist, pandemic, migrant etc.), they can be resolved only by restorative sustainable development, where a substantial role is played by national leaders whose success needs to be examined. Accordingly, the chosen subject of this scientific paper is the study of the ruling success of national leaders, with the aim of contributing both to their efficiency in guiding their own countries and to the resolution of the abovementioned world problems. In that context it should be emphasized that this theoretical research has used a suitable research project in the application of which important new scientific findings have been made about the correlation of political competencies of national leaders and the results achieved in their respective countries.